Association between telomere length in human umbilical cord tissues and polychlorinated biphenyls in maternal and cord serum. (August 2022) - Takahashi, Tomoko; Eguchi, Akifumi; Watanabe, Masahiro; Todaka, Emiko; Sakurai, Kenichi; Mori, Chisato
Abstract: Environmental exposure to persistent organic pollutants during pregnancy has potential adverse health effects on the fetus. One of the environmental pollutants is polychlorinated biphenyl (PCB). Earlier, we reported the presence of PCBs in fetal tissues such as the umbilical cord. Telomere length (TL) is a biomarker of aging because it shortens with each cell division. According to the Developmental Origins of Health and Disease hypothesis, fetal exposure to environmental pollutants during pregnancy affects the occurrence of non-communicable diseases in later life. In the current study, we investigated the association between cord tissue TL and serum levels of PCBs. The subjects were 114 mother-child pairs participating in a birth cohort study, the Chiba Study of Mother and Child Health (C-MACH). Maternal serum was collected during pregnancy, and cord serum and tissue were obtained at birth. TL was assessed by qPCR using genomic DNA extracted from the cord tissue. Maternal and cord serum PCB congener levels were assessed using gas chromatography and negative ion chemical ionization qMS. In male fetuses, serum levels of PCB74 in the cord blood were significantly associated with TL following covariate adjustment, but no significant association was found in female fetuses. These data suggest that the TL of the umbilical cord is affected by fetal exposure to PCBs. Graphical abstract: Image 1 Highlights: We studied the association between fetal PCB exposure and TL in umbilical cord tissue. In male fetuses, cord serum PCB74 levels were significantly associated with TL. Umbilical cord TL may be a marker for PCB exposure and some diseases in later life.